Bagaimana Budaya Membentuk Pengaruh Pendapatan Pasangan Dan Gaya Hidup Terhadap Konsumsi Perhiasan Emas: Studi Kasus Pada Ibu Rumah Tangga Di Kabupaten Sidrap - Muhammad. N, Aksa; Arwin, Arwin; Faradiba, Besse; Alim Fasieh, Muh. (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This research is motivated by the tendency of housewives to acquire gold jewelry—a behavior not solely driven by financial considerations but also shaped by lifestyle preferences and local cultural norms. Conducted in Sidenreng Rappang Regency (Sidrap), a region predominantly inhabited by the Bugis ethnic community where gold holds profound socio-cultural significance, this study aims to evaluate the extent to which husbands’ income and lifestyle influence g old jewelry purchasing behavior, with Bugis cultural values acting as a moderating variable. Employing a quantitative approach, data were collected through questionnaires administered to 100 housewives in Sidrap. Statistical analysis was performed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The findings confirm a significant and positive influence of both husbands’ income and lifestyle on gold jewelry purchasing behavior. Furthermore, Bugis cultural values were found to strengthen the impact of these two factors. The results demonstrate that economic capacity and lifestyle preferences drive gold jewelry acquisition among housewives in Sidrap, while Bugis cultural norms—functioning as a moderator—enhance the strength of these relationships. This highlights the critical role of integrating localized cultural contexts in understanding consumer behavior.